A Socio-Epidemiological Study Of Leprosy In A Leprosy Endemic Rural Population (South India) - Reddy B.N; Bansal R.D (Wolters Kluwer Medknow Publications, 1987)
Various social factors in relation to leprosy were studied in a rural population of Pondicherry Union Territory. The prevalence of leprosy among Harijans was found to be 56.8 / 1000 and among Gounders it was 40.08 / 1000. Highest prevalence of 46.05 / 1000 was found in those whose income was between Rs.100/- and 200/- per month. The prevalence of leprosy was inversely correlated with the education. A positive history of contact was forthcoming in 30.1% of the cases. Only 23.6% of the cases were registered for treatment was 6.30%. There was a change in the social life in 2.09% of the cases and the income had decreased in 3.14% of the cases consequent to the disease.